Cooperative Housing Pioneers in Central and South-Eastern Europe: Mainstreaming Alternatives through Translocal Networks - Corinna Hölzl (Critical Housing Analysis)
Financing remains the most significant challenge for grassroots housing movements in Europe. This is particularly true for housing pioneers in semi-peripheral European countries, where not only is access to adequate financing limited, but appropriate regulatory frameworks and organisational and institutional capacities are also lacking. In response, translocal networks such as MOBA have emerged in Central and South-Eastern Europe to promote non-speculative housing alternatives and, particularly, to establish transnational solidarity-based financing for community-led housing. Against this backdrop, this paper analyses the transscalar strategies of MOBA in their efforts to challenge financialised housing practices.